TRILOGY ACS Outcomes - Alexander, Lori (MD Conference Express, 2012)
In the largest trial to date of patients with medically managed acute coronary syndrome without revascularization, prasugrel did not improve outcomes, compared with clopidogrel during 2.5 years of follow-up among patients <75 years. The findings are from the Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes [TRILOGY ACS] study [Roe MT et al. N Engl J Med 2012].